Preliminary Investigation of LED Lighting as Growth Light for Seedlings from Different Tree Species in Growth Chambers - ASTOLFI, Stefania; MARIANELLO, Chiara; GREGO, Stefano; BELLAROSA, Rosanna (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2012)
The influence of light quality on growth and metabolic activity during pre-cultivation (in miniplug containers) of beech (Fagus sylvatica L.), holm oak (Quercus ilex L.) and wild cherry (Prunus avium) plants was investigated. Seedlings were grown in a growth chamber for a month under light-emitting diode (LED) light or fluorescent light. The LED lamps (Valoya) used in this study emitted a continuous spectrum thanks to a mixture of blue, green, red and far-red LEDs. Our results showed that plant response to light quality seems to be related to the plant species. In particular, in beech seedlings fresh and dry weight, shoot height and leaf area were greatest when plants were cultured under LED light, and lowest under fluorescent lamps. Furthermore, we found that LED-induced reduction of chlorophyll contents in beech and holm oak leaves resulted in an increase of the carboxylase capacity of Rubisco in the same plant species suggesting an improvement of light-use-efficiency in these plants. These results indicate that LED light may be suitable for the culture of plants in tightly controlled environments. The comparison of malondialdehyde levels between LED and fluorescent grown plants strongly supports this idea.
Keywords: beech; glutamine synthetase; Holm oak; light; lipid peroxidation; Rubisco; wild cherry

Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila (Journal of Agricultural and Food Chemistry, 2003)
The gastroprotective effects of 70% acetone extracts of Quercus suber and Quercus coccifera leaves and of tannins (pedunculagin, castalagin, phillyraeoidin A, and acutissimin B) purified from these extracts were examined in the mouse using the ethanol-induced gastric ulcer model. Both extracts (25, 50, and 100 mg/kg), given orally, prevented the formation of ethanol-induced lesions in the stomach. The percent protection varied between 68 and 91%. Purified tannins (50 mg/kg) were also effective in protecting the stomach against ethanol, and the percent protection varied from 66 to 83%. Castalagin was the most potent. Both extracts and all of the tannins tested (10, 25, and 50 ?g/mL) strongly inhibited (55?65%) the lipid peroxidation of rabbit brain homogenate. These results suggest that the gastroprotective effects of extracts of Q. suber and Q. coccifera leaves and the purified tannins in this experimental model are related to their anti-lipoperoxidant properties. Keywords: Experimental gastric ulcer; lipid peroxidation; medicinal plants; Quercus sp.; tannins; castalagin
From Duplicate 2 (Effect of Tannins from Quercus suber and Quercus coccifera Leaves on Ethanol-Induced Gastric Lesions in Mice - Khennouf, Seddik; Benabdallah, Hassiba; Gharzouli, Kamel; Amira, Smain; Ito, Hideyuki; Kim, Tae-Hoon; Yoshida, Takashi; Gharzouli, Akila)
Keywords: Acetone; Animals; Biphenyl Compounds; castalagin; Catechols; Catechols: therapeutic use; Ethanol; Experimental gastric ulcer; Hydrolyzable Tannins; lipid peroxidation; Lipid Peroxidation: drug effects; Male; Medicinal plants; Mice; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: therapeutic use; Plant Leaves; Plant Leaves: chemistry; Quercus; Quercus sp.; Quercus: chemistry; Rabbits; Stomach Ulcer; Stomach Ulcer: chemically induced; Stomach Ulcer: prevention & control; Tannins; Tannins: pharmacology; Tannins: therapeutic use